The i-PEACH framework on the contributing factors of parental vaccine hesitancy towards COVID-19 vaccination in Petaling Selangor - Minhat, Halimatus Sakdiah; Lim, Poh Ying; Zulkifli, Sarah Nabila (Persatuan Pakar Perubatan Kesihatan Awam Malaysia,Malaysian Public Health Physicians Association, 2024)
Since the emergence of the COVID-19 pandemic, vaccination has been regarded as one of the most effective mitigating measures to stop virus transmission. This research seeks to explore the contributing factors of parental vaccine hesitancy against the COVID-19 vaccination among KEMAS preschool parents, Petaling district, Selangor. A qualitative study design, utilizing in-depth interviews was conducted among vaccine-hesitant parents guided by a semi-structured interview protocol. Each interview session was transcribed verbatim and analysed thematically prior to the conduction of the consecutive in-depth interviews. The thematic analysis was performed inductively and deductively based on the constructs of the Health Belief Model (HBM) and Theory of Planned Behaviour (TPP). Related codes and themes were identified, guided by the HBM and TPP constructs. A total of seven vaccine hesitant parents were conveniently sampled for the in-depth interviews, with five themes and 17 subthemes successfully identified. The themes and subthemes were presented as the Integrated Parental Vaccine Hesitancy (i-PEACH) framework. In conclusion, the HBM and TPP provide a solid and comprehensive understanding towards vaccine hesitancy against the COVID-19 vaccination among the KEMAS preschool vaccine hesitant parents, through the development of the i-PEACH framework. These findings may guide targeted public health strategies to increase vaccine acceptance.